Coverage of Children’s Issues in the Nepali Print and Online Media: Impact of Public Pressure on Media Gatekeeping - Aryal, Kundan (Journal of Social Protection, 2021)
The media do not cover all the events and incidents of the day. There is a visible trend across the world that the process of gate keeping in the mass media outlets could be liberal with the presence of pressure groups. Though the usual trend of low media coverage on children in Nepal has been low, the spikes have been visible time and again with frequent and relentless persuasion of the cause in the form of pressure, advocacy and campaigns. Analysis of the media coverage of child-related issues from five national dailies and three prominent online news portals based on the cultivated data with qualitative and quantitative approaches demonstrate the direct relationship between the pressure and coverage. It reveals that influence over the gate keeping process would become the potential to cause wider coverage and prominence placement.